Pengaruh Literasi Finansial dan Pengelolaan Uang Saku Terhadap Perilaku Menabung dengan Kontrol Diri sebagai Variabel Mediasi - Cahya Tri Amirtha Agsania; Eko Wahjudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Internal and external factors can cause each individual to have different characteristics and tendencies in terms of saving. This research aims to determine the influence of financial literacy and pocket money management on saving behavior at the Unesa Faculty of Economics and Business which is mediated by self-control. The purposive sampling technique used in this research was 100 FEB Unesa students. Data collection methods are carried out through test questions and questionnaires. Data processing in this study used SPSS version 25 software, the research results showed that: 1) there is no influence between financial literacy on saving behavior, 2) there is a significant positive influence between financial literacy and self-control, 3) there is a significant positive influence between self-control on saving behavior, 4) there is a significant positive influence between pocket money management on saving behavior, 5) there is a significant positive influence between pocket money management on self-control, 6) self-control is able to mediate financial literacy and pocket money management on saving behavior, 7) Self-control is able to mediate pocket money management on saving behavior.